Ear nose and throat (ENT) aspects of Obstructive Sleep Apnea Syndrome (OSAS) diagnosis and therapy - Passali, Desiderio; Spinosi, Maria Carla; Passali, Francesco Maria (La Medicina del Lavoro, 2017)
This article analyzes the role played by the ear, nose and throat (ENT) specialist in the diagnosis and treatment of the Obstructive Sleep Apnea Syndrome (OSAS). Diagnosis: The instrumental methods of investigation of otolaryngology expertise are fiberoptic rhinolaryngoscopy and sleep endoscopy. To better define and treat OSAS it is essential to define location, extension and degree of obstruction. The major limitation of rhinolaryngoscopy is that it is conducted while the patient is awake. Sleep endoscopy was introduced to address this issue: it is an endoscopic examination conducted during pharmacologically induced sleep (midazolam, propofol). Surgical treatment: The applicability of surgical treatment is limited: it is not efficient for every patient and not to the same extent. Surgical therapy is based on the detection and correction of the site of obstruction, although in most cases the obstruction sites are located at different levels. The surgical approach usually follows a path characterized by “subsequent steps”. According to Stanford University Powell-Riley Protocol the first phase includes: nasal surgery, palate surgery (UPPP, LAUP Laser Assisted uvulopalatoplasty, UvuloPalatalFlap UPF) and tongue base surgery (tongue suspension, genioglossus advancement, hyoid suspension) that could either be executed individually or associated. Four-six months after surgery a physical and polysomnography examination should be performed. In case of symptoms persistence, the surgeon could move on to phase II surgery as recovery therapy. The phase II surgery includes: maxillo-mandibular advancement, tongue base resection and tracheotomy. In selected cases a Phase II surgery could be planned at the beginning of treatment.